Village Fund Tax Compliance: Administrative Formality or Substantive Fiscal Responsibility? - Dita Aulia Buata; Tri Handayani Amaliah; Mahdalena Mahdalena (Jurnal Ekuilnomi, 2026)
Tax compliance in village fund management constitutes a crucial element of fiscal accountability and public financial governance at the local level. In practice, however, tax compliance in village fund management is predominantly understood as the fulfillment of administrative procedures rather than as a form of substantive fiscal responsibility. This study aims to critically examine how tax compliance in village fund management is conceptualized and implemented, specifically whether it functions as an administrative formality or as an expression of substantive fiscal accountability. This study employs a Systematic Literature Review using a narrative-critical approach to the public sector accounting and taxation literature. The findings indicate that the dominance of administratively oriented compliance tends to produce formal and symbolic fiscal accountability. Tax compliance practices are shaped by a combination of individual factors, institutional arrangements, administrative systems, as well as power dynamics and fraud risks. These findings highlight the need for a policy shift from procedural compliance toward the strengthening of substantive tax compliance through capacity building for village officials, risk-based policy approaches, and the reinforcement of public financial governance at the village level